The Influence of Learning Motivation towards English Learning Achievements of 11TH Grade Students at SMA n 3 Jambi City Academic Year 2017/2018 - Intan Aprilia Tamara Halim; Wennyta Wennyta; Khidayatul Munawwaroh (JELT: Journal of English Language Teaching, 2017)
AbstractThe objective of this study was to find out the influence of learning motivation towards English learning achievement. This study involved 269 students of eleventh grade, the sample was 40 students of eleventh grade science six at SMA N 3 Jambi City academic year 2017/2018 and taken by random sampling with lottery. There were two variables in this study, they were learning motivation and English learning achievement with 6 total indicators. The method of this study was survey method of quantitative research. Instrument used in this study was questionnaire and documentation. The research found that mean of students motivation from the questionnaire was valued 81,6 in good category. From the findings, it showed that there was no significant influence of learning motivation towards English learning achievement. Based on the analysis of data, the value of tcount is -0,052 ˂ ttable 2,024 in significance 0,025 line 38 counted by SPSS for Windows Version 16.Keywords: Learning motivation, English learning achievement